Memahami Penciptaan, Perkembangan, dan Tantangan Manusia di Era Digital - Nurhanudin Nurhanudin; Kartimi Kartimi (Journal on Education, 2025)
Humans as creatures created with intellectual potential, creativity and adaptability, have gone through various stages of development in the history of civilization. In the digital era, these capabilities are transforming to face new challenges and opportunities. This article explains the relationship between the concept of human creation in technological development, and how the relevance of both influences the context of the current digital world. Focus is given to the role of humans as creators of technology, the impact of digital developments on human identity, the impact and ethical challenges in facing digital change.